Prefase V International Meeting of Mathematical Education (2021)
The objective of the V International Meeting on Mathematics Education (V IMME) is to create and maintain a space that privileges and promotes the culture of mathematics, reflection and discussion on the education and application of mathematics, statistics, its history, evolution and didactics, and its interrelation with the sciences. At the meeting, researchers, scientists, and mathematics teachers socialize the results of research, consolidate networks for the exchange of successful experiences, to strengthen mathematics education at different educational levels, promote innovation and encourage the creation of policies, models, educational strategies, tools, and techniques in various areas of mathematics. They also promote innovation and encourage the creation of policies, models, educational strategies, tools and techniques in different areas of knowledge, and foster students' interest in research. This academic space has been maintained, so in the first semester of 2017 the First International Mathematics Education Meeting was held, with the presence and participation of teachers, students and professionals from different university, basic and secondary education institutions. During the Summit, researchers carry out activities such as, master conferences, short lectures. In this year 2021, the thematic areas in this meeting were: Mathematics education for science and engineering, Physics-mathematics applied to medicine, Modeling, simulation, and diagnostics, Applied physics-mathematics, Mathematics and statistics, Application of physiochemistry, Computer science, Origami